Altered Circulating Levels of Matrix Metalloproteinases and Inhibitors Associated with Elevated Type 2 Cytokines in Lymphatic Filarial Disease - Anuradha, Rajamanickam (Public Library of Science, 2012)
BACKGROUND: Infection with Wuchereria bancrofti can cause severe disease characterized by subcutaneous fibrosis and extracellular matrix remodeling. Matrix metalloproteinases (MMPs) are a family of enzymes governing extracellular remodeling by regulating cellular homeostasis, inflammation, and tissue reorganization, while tissue-inhibitors of metalloproteinases (TIMPs) are endogenous regulators of MMPs. Homeostatic as well as inflammation-induced balance between MMPs and TIMPs is considered critical in mediating tissue pathology. METHODS: To elucidate the role of MMPs and TIMPs in filarial pathology, we compared the plasma levels of a panel of MMPs, TIMPs, other pro-fibrotic factors, and cytokines in individuals with chronic filarial pathology with (CP Ag+) or without (CP Ag−) active infection to those with clinically asymptomatic infections (INF) and in those without infection (endemic normal [EN]). Markers of pathogenesis were delineated based on comparisons between the two actively infected groups (CP Ag+ compared to INF) and those without active infection (CP Ag− compared to EN). RESULTS AND CONCLUSION: Our data reveal that an increase in circulating levels of MMPs and TIMPs is characteristic of the filarial disease process per se and not of active infection; however, filarial disease with active infection is specifically associated with increased ratios of MMP1/TIMP4 and MMP8/TIMP4 as well as with pro-fibrotic cytokines (IL-5, IL-13 and TGF-β). Our data therefore suggest that while filarial lymphatic disease is characterized by a non-specific increase in plasma MMPs and TIMPs, the balance between MMPs and TIMPs is an important factor in regulating tissue pathology during active infection.